RELATIONSHIP OF VICARIOUS TRAUMATIZATION WITH FAMILY RELATIONS AND COPING STRATEGIES AMONG HEALTHCARE PROFESSIONALS - Nazia Mustafa (Army Medical College Rawalpindi, 2020)
Objective: To study the relationship of vicarious traumatization with family relations and coping strategies among Health care professionals along with to find out the frequency of vicarious traumatization.